Pengaruh kepatuhan pendokumentasian asuhan medis terhadap kelengkapan dokumen pengajuan klaim JKN di Instalasi Rawat Inap RSUD Badung tahun 2018 - Raditya Putra Pratama Suryadhi; Dyah Pradnyaparamita Duarsa; Komang Ayu Kartika Sari (Intisari Sains Medis, 2019)
Background: BPJS as a health insurance institution runs the National Health Insurance (JKN) program. JKN implements a prospective financing system whereby payments made after the provision of services are in accordance with the agreement at the beginning in the form of packages. As regard with the fee, the hospital should take an effort to submit the proof document as the condition for the filing of the claim.Aim: This study aims to determine the effect of medical documenting compliance with the completeness of the JKN claim filing documents at the inpatient installation of Badung Hospital.Method: This study is a cross-sectional analytic study with the sample used is 120 documents of in-patient medical treatment that has been repatriated at the in-patient installation of Badung General Hospital in February 2018. Â Results: This research get result that the price rs = 0.861 and p-value = 0,003.Conclusion: There is an effect of compliance with documenting medical care on the completeness of claim filing documents in the in-patient installation of Badung General Hospital.